Optimisation of casein adsorption onto alkaline-treated rice husk using response surface methodology for sustainable protein recovery - Vincent, Angelina Phoebe; Abdul Rahim, Mohd Badrin Hanizam; Abdul Shukor, Mohd Yunus; Khayat, Mohd Ezuan (University of Malaya, 2024)
With rising environmental concerns and a need for sustainable resource management, protein recovery from dairy wastewater has gained significant attention. This study investigates the use of alkaline- treated rice husk as an adsorbent for casein recovery, offering a low-cost and eco-friendly alternative for waste valorization. Using response surface methodology (RSM) and a Box-Behnken Design (BBD), the effects of contact time, adsorbent dosage, and pH on adsorption capacity were systematically evaluated. Optimal conditions were determined as 30 minutes of contact time, 4 mg/mL adsorbent dosage, and pH 9.93, achieving a predicted adsorption capacity of 111.547 mg/g. Validation experiments confirmed the model’s accuracy, yielding an actual adsorption capacity of 110.0 mg/g, with no significant difference from the predicted values (p > 0.05). These findings demonstrate the potential of alkaline-treated rice husk for efficient protein recovery, contributing to sustainable nutrient recycling and environmental protection. This optimized adsorption process holds promise for industrial applications in waste management within the dairy sector, supporting resource conservation and sustainable practices. However, the study is limited by the lack of long-term stability testing of the adsorbent and its performance in real industrial wastewater, which should be addressed in the future.